2020
DOI: 10.1021/acsami.0c10458
|View full text |Cite|
|
Sign up to set email alerts
|

Chondrocyte-Targeted MicroRNA Delivery by Engineered Exosomes toward a Cell-Free Osteoarthritis Therapy

Abstract: Targeted delivery to the diseased cell or tissue is the key to the successful clinical use of nucleic acid drugs. In particular, delivery of microRNA-140 (miRNA-140, miR-140) into chondrocytes across the dense, nonvascular extracellular matrix of cartilage remains a major challenge. Here, we report the chondrocyte-targeting exosomes as vehicles for the delivery of miR-140 into chondrocytes as a new treatment for osteoarthritis (OA). By fusing a chondrocyte-affinity peptide (CAP) with the lysosome-associated me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
213
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 255 publications
(213 citation statements)
references
References 39 publications
0
213
0
Order By: Relevance
“…The speci c development approaches of the exosomes included surface engineering, genetic engineering, chemical modi cation, and membrane fusion [32][33][34]. Of which the genetic engineering generated overexpression of a speci c protein or micro-RNA and exhibited satisfactory outcome: Chen et al found that the GDNF-modi ed human ADSCs-derived exosomes ameliorated peritubular capillary loss in tubulointerstitial brosis [35]; Sun et al revealed that the exosomes derived from the HIF-1α overexpressed mesenchymal stem cells (MSCs) enhanced the angiogenesis to provide cardioprotection in myocardial infarction [36]; and Wang et al discovered that exosomes derived from miR-155-5poverexpressing synovial MSCs enhanced the bio functions of chondrocytes to prevent osteoarthritis [37].…”
Section: Discussionmentioning
confidence: 99%
“…The speci c development approaches of the exosomes included surface engineering, genetic engineering, chemical modi cation, and membrane fusion [32][33][34]. Of which the genetic engineering generated overexpression of a speci c protein or micro-RNA and exhibited satisfactory outcome: Chen et al found that the GDNF-modi ed human ADSCs-derived exosomes ameliorated peritubular capillary loss in tubulointerstitial brosis [35]; Sun et al revealed that the exosomes derived from the HIF-1α overexpressed mesenchymal stem cells (MSCs) enhanced the angiogenesis to provide cardioprotection in myocardial infarction [36]; and Wang et al discovered that exosomes derived from miR-155-5poverexpressing synovial MSCs enhanced the bio functions of chondrocytes to prevent osteoarthritis [37].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, engineered exosomes have been used for targeted drug delivery (Duan et al, 2021;Liang et al, 2021a). Our studies have already proven the potential of targeted exosomes for miRNA and small molecular delivery in cartilage repair (Duan et al, 2020a;Liang et al, 2020;Xu et al, 2021). The functional components of gRNA and Cas9 protein can be encapsulated in exosomes and they can transmit the gene-editing activity of the CRISPR/Cas9 system intracellularly.…”
Section: Extracellular Vesicles-based Delivery Of Cas9/grnamentioning
confidence: 95%
“…For delivery of microRNA (miR)-140 into chondrocytes across the dense nonvascular extracellular matrix of cartilage, a chondrocyte affinity peptide (CAP) attached to exosomes expressing the lysosome-associated membrane glycoprotein 2b (Lamp2b) protein has been developed. CAP has been shown to successfully deliver miR-140 to deep cartilage regions through the dense mesochondrium in a rat model [47]. Exosomal expression of interleukin 3 fused to Lamp2b was also attempted for targeting chronic myeloid leukemia [48].…”
Section: Expressing System: Lamp-2bmentioning
confidence: 99%